Analisis Pengaruh Financial Literacy, Parent's Income, dan Emotional Intelligence terhadap Financial Behavior pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Esa Unggul - Yatimin; Widiyastuti, Tetty; Jama, Ahmad Kamal (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2025)
The aim of this research is to determine and analyze the influence of financial literacy, parent's income, and emotional intelligence on financial behavior among students at the Faculty of Economics and Business, Esa Unggul University. This research is causal associative research and the type of data used is quantitative data. The population of this research is active students from the Faculty of Economics and Business, Esa Unggul University. The research sample consisted of 100 people. The data analysis technique used is multiple linear regression. The results of this study show that partially analyzing the influence of financial literacy, parent's income, and emotional intelligence has positive and significant effect on financial behavior. The results of the simultaneous analysis show that financial literacy, parent's income, and emotional intelligence have positive and significant effect on financial behavior among students at the Faculty of Economics and Business, Esa Unggul University.